Hydrolysed fumonisin B1 and N-(deoxy-D-fructos-1-yl)-fumonisin B1: stability and catabolic fate under simulated human gastrointestinal conditions. (28th November 2014) - Cirlini, Martina; Hahn, Irene; Varga, Elisabeth; Dall'Asta, Margherita; Falavigna, Claudia; Calani, Luca; Berthiller, Franz; Del Rio, Daniele; Dall'Asta, Chiara
Abstract: Food processing may induce thermal degradation of fumonisins in corn via Maillard-type reactions, or alkaline hydrolysis via loss of the two tricarballylic acid moieties. In the former case, N -(1-deoxy-D-fructos-1-yl)-fumonisin B1 (NDF) can be formed, while the latter derivative is called hydrolysed fumonisin B1 (HFB1 ). The aim of this study was to deepen the knowledge about the gastrointestinal stability of HFB1 and NDF in humans. Due to the lack of standard, NDF was chemically synthesised and cleaned up in high purity to be used for further experiments. While NDF is already partially cleaved (about 41%) during simulated digestion, it remained rather stable towards human colon microflora. In contrast to this, HFB1 is partially metabolised by the colon microflora to unknown compounds after 24 h of fermentation, as seen by a loss of about 22%. Concluding, the cleavage of NDF during digestion as well as the likely metabolisation of HFB1 emphasise the need for animal trials to ascertain their toxicity in vivo .